The Influence of Website Characteristics on a Consumer's Urge to Buy Impulsively - Parboteeah, D. Veena; Valacich, Joseph S.; Wells, John D. (Information Systems Research, 2009)
With the proliferation of e-commerce, there is growing evidence that online impulse buying is occurring, yet relatively few researchers have studied this phenomenon. This paper reports on two studies that examine how variations in a website influence online impulse buying. The results reveal some relevant insights about this phenomenon. Specifically, although many participants had the urge to buy impulsively, regardless of website quality, this behavior's likelihood and magnitude was directly influenced by varying the quality of task-relevant and mood-relevant cues. Task-relevant cues include characteristics, such as navigability, that help in the attainment of the online consumer's shopping goal. Conversely, mood-relevant cues refer to the characteristics, such as visual appeal, that affect the degree to which a user enjoys browsing a website but that do not directly support a particular shopping goal. The implications of the results for both future research and the design of human-computer interfaces are discussed.